Political participation of women. Some confluences between ethics and human rights - Rein Venegas, Tatiana (Acta Bioethica, 2013)
This article explores the links between global ethics and human rights, with a particular focus on women’s political participation, as a way of inquiring into possible ramifications within the field of global ethics. To this end, it determines the scope of the concepts of ethics and global ethics as well as that of human rights. It analyses the links between them, particularly the incorporation of ethical considerations on the part of human rights and the validity that the latter assign to them. Finally, the article concentrates onto women’s rights and more specifically on their political participation. It analyses the diverse alternatives of participation, which cover a range that spans from the traditional parliamentary participation up to forms like the establishment of governmental agendas aimed at improving the condition of women and the participation through women’s movements. It is concluded that, both from an ethics as well as human-rights point of view, it is necessary an evaluation of ways for achieving the implementation of these rights. These can derive from a more permanent incorporation of women’s movements in the decision making process of public policies.